Nanotechnology-Based Vaccines for Allergen-Specific Immunotherapy: Potentials and Challenges of Conventional and Novel Adjuvants under Research - Litty Johnson; Albert Duschl; Martin Himly (Vaccines, 2020)
The increasing prevalence of allergic diseases demands efficient therapeutic strategies for their mitigation. Allergen-specific immunotherapy (AIT) is the only causal rather than symptomatic treatment method available for allergy. Currently, AIT is being administered using immune response modifiers or adjuvants. Adjuvants aid in the induction of a vigorous and long-lasting immune response, thereby improving the efficiency of AIT. The successful development of a novel adjuvant requires a thorough understanding of the conventional and novel adjuvants under development. Thus, this review discusses the potentials and challenges of these adjuvants and their mechanism of action. Vaccine development based on nanoparticles is a promising strategy for AIT, due to their inherent physicochemical properties, along with their ease of production and ability to stimulate innate immunity. Although nanoparticles have provided promising results as an adjuvant for AIT in in vivo studies, a deeper insight into the interaction of nanoparticle–allergen complexes with the immune system is necessary. This review focuses on the methods of harnessing the adjuvant effect of nanoparticles by detailing the molecular mechanisms underlying the immune response, which includes allergen uptake, processing, presentation, and induction of T cell differentiation.